CD4+RORγt++ and Tregs in a Mouse Model of Diet-Induced Nonalcoholic Steatohepatitis - Luisa Vonghia; Nathalie Ruyssers; Dorien Schrijvers; Paul Pelckmans; Peter Michielsen; Luc De Clerck; Albert Ramon; Emilio Jirillo; Didier Ebo; Benedicte De Winter; Chris Bridts; Sven Francque (Hindawi Limited, 2015)
Background and Aims. Inflammatory mediators that cross-talk in different metabolically active organs are thought to play a crucial role in the pathogenesis of Nonalcoholic Steatohepatitis (NASH). This study was aimed at investigating the CD4+RORγt+ T-helper cells and their counterpart, the CD4+CD25+FOXP3+ regulatory T cells in the liver, subcutaneous adipose tissue (SAT), and abdominal adipose tissue (AAT) in a high fat diet (HFD) mouse model. Methods. C57BL6 mice were fed a HFD or a normal diet (ND). Liver enzymes, metabolic parameters, and liver histology were assessed. The expression of CD4+RORγt+ cells and regulatory T cells in different organs (blood, liver, AAT, and SAT) were analyzed by flow cytometry. Cytokine and adipokine tissue expression were studied by RT-PCR. Results. Mice fed a HFD developed NASH and metabolic alterations compared to normal diet. CD4+RORγt++ cells were significantly increased in the liver and the AAT while an increase of regulatory T cells was observed in the SAT of mice fed HFD compared to ND. Inflammatory cytokines were also upregulated. Conclusions. CD4+RORγt++ cells and regulatory T cells are altered in NASH with a site-specific pattern and correlate with the severity of the disease. These site-specific differences are associated with increased cytokine expression.